Maturity Analysis of Governance, Risk, and Compliance (GRC) Implementation at PT Kimia Farma Trading & Distribution - Romi Taofik Sudrajat; Gunardi Endro (Sean Institute, 2025)
In an era of globalization and increasingly fierce competition, companies in Asia, including Indonesia, face increasingly complex challenges in maintaining and improving their position in the market. Competition with other Asian countries is one of the main factors that encourages companies to continue to adapt and improve their performance. In an effort to face this challenge, company management has developed from conventional concepts to focus on governance, risk, and compliance, known as GRC (Governance, Risk and Compliance). The aim of this research is to determine the maturity of the implementation of Governance, Risk and Compliance (GRC) at PT Kimia Farma Trading & Distribution (KFTD). This study utilized qualitative methods to understand and describe the situation that takes place in the research environment. The analysis began with the coding stage of the data derived from the results of the interviews which had been transcribed into text using a case study approach. The research concludes that the maturity level of Governance, Risk Management, and Compliance (GRC) implementation at KFTD is currently at an early stage, with the integration between governance, risk management, and compliance not yet fully achieved. Although the organizational structure and regulatory compliance provide support, GRC functions are still operating separately, and internal awareness and commitment need to be enhanced. A more mature GRC implementation is necessary to improve operational efficiency, decision-making, and ensure business sustainability. Recommendations for KFTD include strengthening GRC socialization programs, developing an integrated GRC system, increasing management support, conducting regular maturity assessments, and leveraging technology for monitoring and reporting.